Characterization Of Phyto-Synthesized Silver Nanoparticles And Their Antimicrobial Activity Against Diabetic Foot Ulcer Bacterial Isolates.: Life Sciences-Silver Nanoparticle against Diabetic foot ulcer microbes - Chhajed Shweta; Arora Asha (International Journal of Life Science and Pharma Research, 2022)
Diabetic Foot Ulcer (DFU) is one of the major complications of Diabetes. Patients with Diabetic Foot ulcers have a high susceptibility to microbial infections and are the leading cause of hospitalization and amputation of lower limbs. In the era of increased prevalence of bacterial resistance and outbreak of resistant infectious diseases, it is very essential to develop effective therapeutic strategies towards multi-drug resistant pathogens. The antimicrobial properties of silver nanoparticles have been well studied, therefore their use in biomedicine and pharmacology is a trend. Herein we present the use of Phyto-mediated synthesized AgNPs for the treatment of diabetic foot ulcers by topical administration. The nanoparticles were synthesized by reducing silver nitrate using Terminalia chebula fruit extract. The nanoparticles were analyzed and characterized using UV-Visible Spectrophotometer, FTIR, XRD, SEM with EDAX, TEM, and DLS. The synthesized silver nanoparticles were assayed for antimicrobial activity against five Diabetic Foot Ulcer bacterial isolates i.e. Escherichia coli, Klebsiella Pneumoniae, Pseudomonas aeruginosa, Streptococcus aureus, and Bacillus subtilis. The bactericidal property of synthesized nanoparticles was analyzed by the Agar well diffusion method, which revealed the remarkable antimicrobial effects against all the selective pathogenic bacterial isolates of Diabetic foot ulcers in the present study. These results constituted the basis for further studies on the use of plant-based silver nanoparticles for the treatment of Diabetic Foot ulcers from different origins.